“Black Music” in the Maghrib: Communities, Practices, and Performance beyond Rouanet - Tamara Dee TURNER (Turath)
Based on extensive and award-winning ethnographic fieldwork on Algerian dīwān spanning 2013 until 2022, this essay engages with Rouanet’s writings on dīwān, both in terms of his colonial language and judgments but also in order to correct and confirm useful historical connections such as pointing out the rich and diverse dīwān scene across Algeria. Turner gives examples of the most current dīwān practices today while showing how at least three schools of practice link back to heterogenous trans-Saharan caravan routes. For example, Eastern Algerian “dīwān” is an almost entirely different practice than dīwān in the west. It connects more to Sidi Merzug that Sidi Bilal while focusing on percussion rather than the ginbrī (three-stringed lute) and one-on-one musical diagnosis – similar to another Algerian ritual known as neshra—rather than the large group therapeutic practices of western dīwān.